2017
DOI: 10.1007/s00431-017-3026-5
|View full text |Cite
|
Sign up to set email alerts
|

Diet in pregnancy—more than food

Abstract: High food quality, together with adequate macro- and micronutrient intake in pregnancy, is crucial for the health status of the mother and child. Recent findings suggest that it could also be beneficial or harmful in the context of the well-being of the whole future population. According to the developmental origins of health and disease hypothesis, most conditions that occur in adulthood originate in foetal life. Moreover, some epigenetic events, modified inter alia by diet, impact more than one generation. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 34 publications
0
56
0
5
Order By: Relevance
“…The recommended type of fatty acid during pregnancy are docosahexaenoic acid and eicosapentaenoic acid, which are beneficial for fetal brain development and proper functioning of the retina (Danielewicz et al 2017). The major fat source of subjects were saturated fatty acid because most of the subjects consumed fried food in their daily food intake.…”
Section: Maternal Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended type of fatty acid during pregnancy are docosahexaenoic acid and eicosapentaenoic acid, which are beneficial for fetal brain development and proper functioning of the retina (Danielewicz et al 2017). The major fat source of subjects were saturated fatty acid because most of the subjects consumed fried food in their daily food intake.…”
Section: Maternal Characteristicsmentioning
confidence: 99%
“…Complex carbohydrate is recommended for pregnant women to improve the function of gut microbiome (Danielewicz et al 2017). Maternal carbohydrate source in this study were mostly simple carbohydrate in the form of white rice or flour-based food.…”
Section: Maternal Characteristicsmentioning
confidence: 99%
“…The prenatal and perinatal periods are sensitive times for women as they are undergoing physiological changes (Soma-Pillay et al, 2016;Talbot & Maclennan, 2016) and experiencing drastic lifestyle changes (relating to sleep, diet, exercise, etc.) (Barakat et al, 2015;Chien & Ko, 2004;Danielewicz et al, 2017;Hall et al, 2009), and with the introduction of harmful toxic chemicals to their bodies, this has been shown to ultimately affect their mental health well into the postpartum period, resulting in the experience of major depressive symptoms. The importance of recognizing the harmful effects of tobacco exposure during the prenatal and perinatal periods will further advance research in the investigation of this association and will hopefully create awareness of relating tobacco exposure to mental health.…”
Section: Main Findingsmentioning
confidence: 99%
“…Maternal diet in pregnancy encompasses more than food intake alone because high food quality and adequate nutrient intake during the perinatal period are critical for maternal and infant health. 28,29 A "Western" diet, which is generally poor in fiber and rich in saturated fats and carbohydrate sweeteners, is considered to be an environmental risk factor, increasing the prevalence of FA. 9,30 Moreover, high trans fat intake, as a typical part of the "Western" diet, is suggested to play a role in the development of childhood asthma, AD, and sensitization in a previous study that did not assess dietary patterns or FA.…”
Section: Maternal Confectionery Dietary Pattern and Trans Fat Associamentioning
confidence: 99%
“…47 Thus, if maternal dietary patterns are generally consistent throughout pregnancy and the first 6 months of breastfeeding, the harmful effects of the maternal confectionery diet may be passed to the infant through breastfeeding, and this may add to the in utero effect of maternal diet that occurs during pregnancy. 29 It has been reported that mothers with high levels of…”
Section: Maternal Confectionery Dietary Pattern and Trans Fat Associamentioning
confidence: 99%